Концепція «обов’язок захищати» як гарантія захисту основоположних прав людини в міжнародному праві - Любашенко, В'ячеслав Ігорович; Любашенко, Вячеслав Игоревич; Liubashenko, Vyacheslav I. (Одеса, 2017)
Дисертація на здобуття наукового ступеня кандидата юридичних наук за спеціальністю 12.00.11 – міжнародне право. – Національний університет «Одеська юридична академія». – Одеса, 2017. Дисертацію присвячено дослідженню генезису, доктринальних поглядів на концепцію «обов’язок захищати», юридичної природи, особливих правових характеристик концепції «обов’язок захищати» як гарантії захисту основоположних прав людини в міжнародному праві, детально проаналізовані окремі елементи концепції з теоретичного та практичного боку. Концепція «обов’язок захищати» у сучасному вигляді складається з чотирьох стовпів: обов’язку держави захищати власне населення від порушень прав людини ad extra; обов’язок міжнародного співтовариства допомагати державі у виконанні її первинного обов’язку; обов’язок міжнародного співтовариства реагувати на невиконання державою свого первинного обов’язку, у тому числі, військовою акцією; та обов’язок міжнародного співтовариства відновлювати постконфліктну країну. В дослідженні приділено значну увагу правовому аналізу військової інтервенції в треті країни від імені міжнародного співтовариства, її місцю в концепції «обов’язок захищати» та відмінності від гуманітарної інтервенції; також розглянуті актуальні правові проблеми військової інтервенції і шляхи правового вдосконалення існуючих норм.

Диссертация на соискание научной степени кандидата юридических наук по специальности 12.00.11 – международное право. – Национальный университет «Одесская юридическая академия». – Одесса, 2017. Диссертация посвящена исследованию генезиса, доктринальных взглядов на концепцию «обязанность защищать», юридической природы,особых правовых характеристик концепции «обязанность защищать» в качестве гарантии защиты основополагающих прав человека в международном праве, детально проанализированы отдельные элементы концепции с теоретической и практической стороны. Концепция «обязанность защищать» в современном виде состоит из четырех столпов: обязанности государства защищать собственное население от нарушений прав человека ad extra; обязанность международного сообщества помогать государству в выполнении его первичной обязанности; обязанность международного сообщества реагировать на невыполнение государством своей первичной обязанности, в том числе, военной акцией; и обязанность международного сообщества восстанавливать постконфликтную страну. В исследовании значительное внимание уделено правовому анализу военной интервенции в третьи государства от имени международного сообщества, её месту в концепции «обязанность защищать» и отличию от гуманитарной интервенции; также рассмотрены актуальные правовые проблемы военной интервенции и пути правового усовершенствования существующих норм.

The thesis for the degree of Candidate of Sciences in specialty 12.00.11 – International law. – National University «Odessa Law Academy». – Odessa, 2017. The thesis presents a research of genesis, doctrinal foundations, legal nature and specific legal characteristics of the ‘responsibility to protect’ concept as a guarantee for human rights protection in international law. The paper highlights the evolution of the ‘responsibility to protect’ concept and its roots in international law, the peculiarities of its legal nature and elements in international law. The ‘responsibility to protect’ concept derives from the theory and practice of humanitarian intervention in XX century. It was presented firstly in 2001 Report of International commission on intervention and state sovereignty «Responsibility to Protect». Legally it was confirmed as a norm of soft international law in World Summit 2005 Outcome Document and practically was implemented in full strength in Libya 2011. From the perspective, 22 ‘responsibility to protect’ inherits causalities of humanitarian intervention (military action), and nowadays debates concerned control of military intervention, criteria for launching military intervention, intervention with authorization ex post facto, right of veto in UN SC are main difficulties for implementation of ‘responsibility to protect’. The author analyses positions of different states and their approach towards military intervention in third states, security paradigms and ‘responsibility to protect’ concept, their activity in UN and other international organizations. In addition, the author examines correlations of ‘responsibility to protect’ with other concepts, such as human security and protection of civilians. The author considers modern structure of the ‘responsibility to protect’ concept, which consists, as proposed by UN General Secretary, of three main components (pillars): State’s responsibility to protect its own population from the threat of genocide, ethnic cleansing, war crimes and crimes against humanity; the responsibility of the international community to assist a State in carrying out its primary responsibility; the responsibility of the international community to respond to the failure of state within its primary responsibility, including military action. This structure is complemented by the not commonly recognized responsibility of the international community to rebuild the post-conflict country, which initially was a part of ‘responsibility to protect’, but was included in common peacebuilding. The research describes the main characteristics of the international legal ‘responsibility to protect’ concept and detailed analysis of the particular elements of the concept within theory and practice of their implementation. The thesis provides close legal examination of state’s sovereignty and primary responsibility of the state to provide security towards its own population through the analysis of international conventions and practice of their application in practice by several judicial and quasi-judicial bodies. As well, the author analyzed early warning, preventive toolbox (root cause prevention and direct prevention efforts), measures, short of military action and military action as components of the corresponding responsibility to protect of international community. Special attention dedicated to the ‘responsibility to rebuild’, its legal nature, place in ‘responsibility to protect’ concept and principles of the ‘responsibility to rebuild’ as a special legal area.
дис. ... канд. юрид. наук : 12.00.11
Любашенко В. І. Концепція «обов’язок захищати» як гарантія захисту основоположних прав людини в міжнародному праві : дис. ... канд. юрид. наук : 12.00.11 / В’ячеслав Ігорович Любашенко ; наук. кер. канд. юрид. наук, доцент М. І. Пашковський ; Нац. ун-т "Одеська юридична академія". - Одеса, 2017. - 263 с.
Любашенко В. І. Концепція «обов’язок захищати» як гарантія захисту основоположних прав людини в міжнародному праві : автореф. дис. ... канд. юрид. наук : 12.00.11 / В’ячеслав Ігорович Любашенко ; наук. кер. канд. юрид. наук, доцент М. І. Пашковський ; Нац. ун-т "Одеська юридична академія". - Одеса, 2017. - 22 с.
Keywords: концепція «обов’язок захищати»; юридичний зміст концепції «обов’язок захищати»; право міжнародної безпеки; право ООН; військова інтервенція в треті країни; превентивна діяльність міжнародних організацій; механізми реагування на порушення імперативних норм міжнародного права; концепция «обязанность защищать»; юридическое содержание концепции «обязанность защищать»; право международной безопасности; право ООН; военная интервенция в третьи страны; превентивная деятельность международных организаций; механизмы реагирования на нарушение императивных норм международного права; the ‘responsibility to protect’ concept; legal content of the ‘responsibility to protect’ concept; the law of international security; the UN law; military intervention in third states; preventive activities of international organizations; mechanisms of reaction towards violations of peremptory norms of international law